A Simple Paper-Based Microfluidic Device for the Rapid Detection of Inorganic Chemicals - Buthaina A. Al Mashrea; Maitha Alrashdi; Nemat Dek Al-Bab; Mohamad Al-Farooq; Hajar Abdalla; Kifah Al Taqaz; Amin Botmah; Mussab Ahmed; Ayad Turky; Ahmed Almehdi; Samar Damiati (Proceedings)
Microfluidic technology, also known as lab-on-a-chip, enables the fabrication of low-cost, user-friendly, and portable detection devices. Microfluidic chips can be utilized for detecting biological and chemical analytes in various liquid samples, including water or biofluids such as urine, blood, and sweat. The specific and quantitative detection of ions has garnered increased attention in recent years due to their potential harm to environmental and human health. Inorganic ions are special chemicals that hold positive or negative charges with relatively small molecular weights. Among the various types of microfluidic platforms, paper-based systems are favored as simple analytical tools that rely on the generation of hydrophilic–hydrophobic contrast on filter paper. In this study, a paper-based microfluidic device was developed as an analytical tool for quantifying several ions, such as iron (Fe3+). The reaction spot was created by simply melting a wax crayon to form hydrophobic barriers that define hydrophilic zones. After spotting Fe3+ samples and potassium thiocyanate (KSCN) as a detection reagent on the reaction zone, an immediate and obvious color change was observed with different ion concentrations ranging between 50 and 500 ppm. While the naked-eye detection of color change was easy at high concentrations, quantifying ion concentrations in samples required the use of a smartphone camera. The captured images were then analyzed using ImageJ software (Java 1.8.0-internal (32-bit)). The developed paper-based microfluidic device exhibited good performance in quantifying Fe3+ ions in samples. Indeed, this simple platform is easy to store and transport, and allows the transportation of aqueous solutions without the need for external pumping or a power supply.